A study on the factors that influence the successful implementation of TQM in a public organization / Nurul Huda Haji Johar - Johar, Nurul Huda (2004)
Overall of the study, TQM is a proven systematic approach to the planning and management of activities which the improvement of the organization's business practices as well as the quality of its product and services. However, not many organizations are able to implement TQM effectively and successfully due to the lack of information and data on the critical success factors. For that reason, these studies are examines the factors that influence the successful implementation of TQM in a public organization. The study focuses on the employees at Kastam, Ayer Keroh, Melaka. Besides have administered questionnaires and interviewing, other methods of research that have been applied in this study are data collection, stratified random sampling technique and also Statistical Package for Social Sciences (SPSS). Hopefully the finding can aid Kastam towards the successful implementation of TQM in their organization. Result from the finding and analysis which had been done, it shows that cooperation factors be at the highest ranking among the others factors that influence the implementation of TQM.